THE MEANING OF EMPLOYEE WELL-BEING IN THE EYES OF MILLENNIALS: A QUALITATIVE EXPLORATION OF THE ROLE OF SUPERVISOR SUPPORT AND WORK-LIFE BALANCE AT PT SANJAYA PUTRA PRATAMA - Adinda Tya Agustina; Iing Sri Hardiningrum (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research aims to explore the meaning of employee well-being as perceived by millennial generation employees through a qualitative approach with a phenomenological paradigm. The main focus of this research is to understand how millennials' subjective experiences of supervisor support and work-life balance shape their interpretation of work well-being. Data were collected through in-depth interviews with a number of participants aged 25–40 years who are actively working in the formal sector. Analysis was conducted using a thematic approach to identify patterns of meaning that emerged from participants' experience narratives. The research results show that employee well-being is understood not only as a stress-free condition or the fulfillment of basic needs, but also as an experience that reflects a sense of being valued, emotional connection with supervisors, and the ability to maintain harmony between work roles and personal life. These findings underscore the importance of relational roles in organizations and the need for work-life balance policies that are more adaptive to the characteristics of the millennial generation.